Photogalvanic Effect of Maltose/Methylene Blue System in Aqueous Methanol - Azmat, Rafia; Uddin, Fahim (Asian Journal of Chemistry, 2012)
Photocurrent was observed during reduction of methylene blue with maltose into leuco methylene blue. The dye molecules presumably function as an energy or electron relay. In this study, the details of the novel transmitted light intensity during reduction of methylene blue into leuco form with reducing sugar maltose is reported, including their absorption maxima, quantum yields and lifetimes of the triplet transient species. Results showed that this transmitted light intensity depended upon the concentration of reducing sugar, solution acidity and temperature. High power mercury lamp was used as a source of radiation for this investigation. This is strikingly visible example of the conversion of light to chemical energy and finally into electrical energy which when pass through reaction cell strike on photocell where electrons are generated, measured as a current on a galvanometer.